2021
DOI: 10.1016/j.annonc.2021.08.474
|View full text |Cite
|
Sign up to set email alerts
|

193P Adjuvant endocrine therapy in patients with breast cancer: Relationship between side effects, quality of life and treatment adherence

Abstract: Background: Several studies have shown improvement in pCR rate with the addition of carboplatinum to the neo-adjuvant chemotherapy (NACT) treatment of stage I-III triple-negative breast cancer (TNBC). However, data on its effects on long-term outcomes such as relapse-free survival and overall survival is not well known. Furthermore, data from ongoing studies addressing these outcomes are currently awaited. We intended to assess pCR, RFS, and OS in this population using our realworld data. abstracts Annals of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In early breast cancer, low rates of adherence to oral hormonal therapy have been linked to reduced survival and potentially quality of life. 7380 While the retrospective analysis by Cindolo et al 65 failed to demonstrate an association between OS and adherence rates ( p = 0.98), Banna et al 48 found an association between nonadherence and radiological response by receiver operating characteristic curve analysis but not with radiological progression-free survival or OS. A strong correlation between OS and duration of abiraterone treatment was identified by Al-Ali et al 62 in their retrospective analysis of the claims database from the largest insurance company in Austria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early breast cancer, low rates of adherence to oral hormonal therapy have been linked to reduced survival and potentially quality of life. 7380 While the retrospective analysis by Cindolo et al 65 failed to demonstrate an association between OS and adherence rates ( p = 0.98), Banna et al 48 found an association between nonadherence and radiological response by receiver operating characteristic curve analysis but not with radiological progression-free survival or OS. A strong correlation between OS and duration of abiraterone treatment was identified by Al-Ali et al 62 in their retrospective analysis of the claims database from the largest insurance company in Austria.…”
Section: Discussionmentioning
confidence: 99%
“…In early breast cancer, low rates of adherence to oral hormonal therapy have been linked to reduced survival and potentially quality of life. [73][74][75][76][77][78][79][80] While the retrospective analysis by Cindolo et al 65 failed to demonstrate an association between OS and adherence rates (p = 0.98), Banna et al 48 found an association between…”
Section: Does Poor Adherence Affect Clinical Outcomes In Advanced Pro...mentioning
confidence: 99%